Summary Congress of German orthopedic and trauma surgeons (DKOU 2017) - Loskutov, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2018)
From 24 to 27 October 2017 in Berlin the annual congress of orthopedists, of German matologists.